Understanding the Role of Economic Education on Generation Z's Lifestyle and Interest in Saving: Why Do Financial Literacy and Circle of Friends Matter? - Muhammad Hasan; Kurniawati Kurniawati; Nurdiana Nurdiana; Nurjannah Nurjannah; Andi Caezar To Tadampali (Dinamika Pendidikan, 2024)
The lifestyle of the people of a country can also be an illustration of how that country will experience growth in the economic sector. An individual's lifestyle and interest in saving must, of course, be accompanied by knowledge and literacy that can control this. This research aims to determine the influence of economic education on the generation's lifestyle and interest in saving, which is mediated by financial literacy and a circle of friends. The population in this study is generation Z, who live in Petasia District. The sampling technique used the Limeshow equation formula with a determined sample size of 700 respondents. The data collection method uses a questionnaire. The data analysis technique is partial least squares structural equation modeling (PLS-SEM) analysis. The results of this research show that economic education (X) has a positive and significant influence on Generation Z's lifestyle and interest in saving. Then, financial literacy and a circle of friends are able to mediate the influence between economic education and Generation Z's interest in saving. These findings encourage generation Z to optimize economic education, both formal and informal, as well as increase financial literacy, in order to maintain their lifestyle. It is also necessary to optimize learning access and provide great opportunities for Generation Z to increase their financial literacy.